Preservation of digital archaeological, GIS and visualisation data - Stančić, Hrvoje (Array, 2011)
Digital cultural heritage objects, like those created on the basis of the archaeological and GIS data, should be actively preserved in the long-term. Visualisations created using that data represent valuable resources for present and future users and researchers. Long-term digital preservation in the environment of constant technological change is a challenging task. The author offers insight into the problem, analyses five applications and services that could help achieve that task and suggests the proper procedures.